CONVERSATIONAL IMPLICATURE FOUND IN STUDENTS’ CONVERSATIONS OF PRAGMATIC CLASS - Liliyan, Awdrey Nanda; Sabat, Yulyanto; Sari, Endah Alam (Premise: Journal of English Education and Applied Linguistics, 2023)
Pragmatics is a relatively new branch of linguistics. Pragmatics can be interpreted as a branch of linguistics that studies the meaning intended by speakers or, more often, studying language in terms of language speakers. Language plays an important role in communication. This role will impact the interlocutor's acceptance of the speaker. Sometimes, spoken language functions in a different form. What is said with what is intended is sometimes different. This study will be discussed in conversational implicature. Conversational implicature tries to analyze a conversation to obtain its true meaning. The concept of conversational implicature explains the differences between what is said and what is implied. Humor is the mental ability to find, express, or appreciate something funny or uncommon. Each implicature has a specific intent and purpose by each speaker.